Investigating the vulnerability and the risks of adolescents in the midst of STD/ HIV/ Aids in their several contexts – a exploratory study - Torres, Cibele Almeida; Barbosa, Stella Maia; Barroso, Maria Grasiela Teixeira; Pinheiro, Patrícia Neyva da Costa (Online Brazilian Journal of Nursing, 2008)
We understand that adolescence is a period of several transformations. We objectify in this study to investigate the vulnerability and the risks of adolescents in the midst of ST/HIV/Aids in their several contexts. It was used the exploratory method, and based on a cultural and ethnographical approach, developed in an elementary and high school in Fortaleza, Ceará, in the period between April and June, 2007. The following instruments were used to work with the 20 selected adolescents observation, participant observation, field diary, focal group. The students of this study were divided into two focal groups according to the gender. There were five meetings with the average duration of 90 minutes. For the data analysis, it was used the content analysis of Bardin. As a result, it is possible to emphasize that social groups are essential in adolescents’ formation of knowledge related to STD/HIV/Aids, however there is a deficit of reflexive and constructive dialogue in these spaces, which are not performing their real roles. This problem together with womanly submission, culturally rooted, influences the risk and vulnerability that expose the adolescents. Therefore, it was concluded that the society as a whole needs to reflect on these factors, distinguishing its roles in the control of STD/HIV/Aids of the adolescents as well as of the population in general, aiming health promotion.